SPECIALIZED TRANSLATION: THEORY AND LINGUODIDACTIC PRINCIPLES OF TEACHING - Bakirova, Khilolakhon (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
In today’s context, the speed of information exchange in fields such as medicine, law, engineering and IT demands of translators not only general linguistic competence but also domain knowledge, terminological precision and context management skills. Therefore, the teaching of specialized translation should be grounded in a model that integrates linguodidactic foundations, a functional-pragmatic approach and technological preparedness. The aim of this study is to clarify the essence of specialized translation, substantiate the linguodidactic principles of its instruction and propose a practical model for implementation in the curriculum. To achieve this aim, several tasks are addressed: systematizing the criteria of terminological precision, contextual fidelity and goal adequacy; aligning Skopos, cognitive-pragmatic and competence-based approaches with the instructional model; demonstrating the role of CAT tools, corpora and term banks in training; mapping progressive competences based on the PACTE model; and proposing course design and assessment criteria for higher education. Methodologically, the article employs a descriptive-analytical design that includes analysis of theoretical sources, expert evaluation of students’ written translations of specialized texts, classroom observations, coding of terminological errors and functional adequacy, and an experimental component using CAT and corpus tools. The findings show that the most frequent errors cluster around terminological consistency and contextual alignment. Integrating CAT and corpus resources into instruction increased consistency and reduced time expenditure. Skopos-driven tasks improved audienceappropriate stylistic choices. Stage-based training aligned with PACTE framework effectively activated strategic competence. Moreover, when the teacher’s role shifted from controller to facilitator, learning outcomes improved and became more consistent The effectiveness of teaching specialized translation rests on five pillars: professional orientation, a terminological approach, contextual grounding, technological preparedness and stepwise competence development. Implementing these principles through curricula, assessment rubrics and portfolios based on real tasks substantially increases the functional adequacy of translations.